2022
DOI: 10.3390/jcm11185352
|View full text |Cite
|
Sign up to set email alerts
|

Open Partial Laryngectomies: History of Laryngeal Cancer Surgery

Abstract: Historically, surgery was the first-choice therapy for early, intermediate and advanced laryngeal squamous cell carcinoma (LSCC). Partial laryngeal surgery has evolved in recent decades and was influenced by many historic events and the development of new technologies. Partial laryngectomies may be performed by open, endoscopic or transoral robotic approaches. In this historic paper, we describe the evolution of open partial laryngectomy techniques, indications and surgical outcomes. Since the first partial la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The survival status of laryngeal cancer patients has been significantly improved. Early laryngeal cancer 23 , 24 can be treated with hemilaryngectomy, preserving some of the laryngeal organs. Lee et al 25 A retrospective analysis of 119 patients with organ preservation (OP) compared stage I total laryngectomy and OP in patients with locally advanced T3/T4a laryngeal cancer The overall survival rates of total laryngectomy and OP patients were similar, with most patients able to maintain a normal diet after total laryngectomy and a higher local recurrence rate in OP patients.…”
Section: Discussionmentioning
confidence: 99%
“…The survival status of laryngeal cancer patients has been significantly improved. Early laryngeal cancer 23 , 24 can be treated with hemilaryngectomy, preserving some of the laryngeal organs. Lee et al 25 A retrospective analysis of 119 patients with organ preservation (OP) compared stage I total laryngectomy and OP in patients with locally advanced T3/T4a laryngeal cancer The overall survival rates of total laryngectomy and OP patients were similar, with most patients able to maintain a normal diet after total laryngectomy and a higher local recurrence rate in OP patients.…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic standpoint, a number of studies have clearly demonstrated the survival benefit of salvage surgical resection in advanced HNC, because it helps to achieve maximum tumor control and functional preservation. [18][19][20][21][22] Unfortunately, only a few studies have demonstrated the potential survival benefit of CDS in patients with M1 HNC, 7,23 and there is a lack of relevant research identifying which patients may benefit most from CDS treatment. In recent years, several studies have supported the survival benefit of CDS in metastatic pancreatic cancer and metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these concerns, several partial laryngectomy techniques have been developed over the years, the first of which dates back to 1788 4 . Vertical laryngectomy, also called hemilaryngectomy, is a partial laryngectomy technique known since the 1800s that was proposed for lateral laryngeal tumors 3–5 . This surgical technique is used for cancers involving the true vocal cord, false cord, subglottic region, and sometimes epiglottis, through a surgical access obtained with a laryngofissure 2,6–8 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the objective of laryngeal oncologic surgery is not only to remove the tumor, but also, as far as possible, to preserve the organ and its functions 2,3 . To overcome these concerns, several partial laryngectomy techniques have been developed over the years, the first of which dates back to 1788 4 . Vertical laryngectomy, also called hemilaryngectomy, is a partial laryngectomy technique known since the 1800s that was proposed for lateral laryngeal tumors 3–5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation